Thinking Outside of the (Search) Box - Dumais, Susan (2015)
With every passing year, more information becomes available online. This is creating a renaissance in human knowledge and our understanding of the world, but it also makes it more difficult to navigate and find what's pertinent. Since 1997, Susan Dumais has been studying these issues as part of Microsoft Research. She will discuss new innovations that will transform research as we know it today by understanding natural language and context, providing answers rather than links, and supporting requests reliant upon images or speech, leading to such breakthroughs as the translation of verbal conversations in real time.
Seattle Technology Alliance: Technology & Discovery Series